Effectiveness and cost of integrated cognitive and balance training for balance and falls in cerebellar ataxia: a blinded two-arm parallel group RCT - Winser, Stanley J.; Chan, Anne Y. Y.; Whitney, Susan L.; Chen, Cynthia H.; Pang, Marco Y. C. (Frontiers in Neurology, 2024)
Background In patients with cerebellar ataxia (CA), dual-tasking deteriorates the performance of one or both tasks. Objective Evaluate the effects of 4 weeks of cognitive-coupled intensive balance training (CIBT) on dual-task cost, dynamic balance, disease severity, number of falls, quality of life, cognition and cost among patients with CA. Methods This RCT compared CIBT (Group 1) to single-task training (Group 2) among 32 patients with CA. The intervention included either dual-task (CIBT) or single-task training for 4 weeks followed by 6 months of unsupervised home exercises. Dual-task timed up-and-go test (D-TUG) assessed dual-task cost of the physical and cognitive tasks. Assessment time points included baseline 1 (Week 0:T1), baseline 2 (Week 6:T2), post-intervention (Week 10:T3), and follow-up (Week 34:T4). Results Compared to single-task training CIBT improved the dual-task cost of physical task [MD −8.36 95% CI (−14.47 to −2.36, p < 0.01), dual-tasking ability [−6.93 (−13.16 to −0.70); p = 0.03] assessed using D-TUG, balance assessed using the scale for the assessment and rating of ataxia (SARAbal) [−2.03 (−4.04 to −0.19); p = 0.04], visual scores of the SOT (SOT-VIS) [−18.53 (−25.81 to −11.24, p ≤ 0.01] and maximal excursion [13.84 (4.65 to 23.03; p ≤ 0.01] of the Limits of Stability (LOS) in the forward direction and reaction time in both forward [−1.11 (−1.42 to −0.78); p < 0.01] and right [−0.18 (0.05 to 0.31); p < 0.01] directions following 4 weeks of training. CIBT did not have any additional benefits in reducing the number of falls, or improving disease severity, quality of life and cognition. The mean cost of intervention and healthcare costs for 7 months was HKD 33,380 for CIBT group and HKD 38,571 for single-task training group. Conclusion We found some evidence to support the use of CIBT for improving the dual-tasking ability, dual-task cost of physical task and dynamic balance in CA. Future large fully-powered studies are needed to confirm this claim. Clinical trial registration https://clinicaltrials.gov/study/NCT04648501, identifier [Ref: NCT04648501].